Adherence to quality measures improves survival in esophageal cancer in a retrospective cohort study of the national cancer database from 2004 to 2016 - Adhia, Akash (J Thorac Dis, 2020)
BACKGROUND: We assessed adherence to four novel quality measures in patients with stage III esophageal cancer, a leading cause of death among GI malignancies. METHODS: We performed a retrospective cohort study of 22,871 stage III esophageal cancer patients identified from the National Cancer Database (NCDB) between 2004 and 2016. Four quality measures were defined from published guidelines: administration of induction therapy, >15 lymph nodes sampled, surgery within 60 days of neoadjuvant treatment, and R0 resection. The association of patient demographic and treatment variables with measure adherence was assessed using multiple logistic regression. Risk of all-cause mortality was assessed comparing adherent and non-adherent cases using Cox modeling. Kaplan-Meier survival estimates of groups that adhered to zero to four out of four quality measures were performed. RESULTS: Adherence was high for neoadjuvant treatment (93.7%), timing of surgery (85.7%) and completeness of resection (92.0%), but low for nodal evaluation (45.9%). Medicaid insurance status was associated with decreased odds of adherence for neoadjuvant treatment [odds ratio (OR) 0.73, 95% confidence interval (CI): 0.54–0.99], nodal evaluation (OR 0.81, 95% CI: 0.68–0.96), and completeness of resection (OR 0.71, 95% CI: 0.54–0.92). From 2010 to 2016, when compared to cases from 2004 to 2005, there was a progressive increase in the odds of adequate induction therapy, nodal staging, and completeness of resection, but a progressive decrease in odds of well-timed surgery. Adherence was associated with decreased all-cause mortality for induction therapy, nodal staging, and R0 resection, but not for timing of surgery. Survival improved as the number of quality measures an individual patient adhered to increased. CONCLUSIONS: Adherence to quality measures is associated with improved survival in patients with stage III esophageal cancer. Understanding variability in measure adherence may identify targets for quality improvement initiatives.